2021
DOI: 10.1029/2021gl095412
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Quasi‐Biennial Oscillation to Historical Volcanic Eruptions

Abstract: It is well-appreciated that large tropical eruptions impact the atmosphere. Injected sulfate aerosols cool the surface and warm the lower stratosphere through absorption of shortwave radiation (Robock, 2000). The impacts of this forcing on the troposphere and extratropical stratosphere have received a great deal of attention, including: an acceleration of the polar vortex (e.g., Graf et al., 1993), changes to planetary waves (e.g., Stenchikov et al., 2002), a reduction in global precipitation (e.g., Iles et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
6
2
Order By: Relevance
“…This result is very different from many previous findings using models in which an intensified BDC was shown (e.g., Abalos et al., 2015; Aquila et al., 2013; DallaSanta et al., 2021; Kinne et al., 1992; Pitari, 1993; Pitari & Mancini, 2002; Toohey et al., 2014). However, Garfinkel et al.…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…This result is very different from many previous findings using models in which an intensified BDC was shown (e.g., Abalos et al., 2015; Aquila et al., 2013; DallaSanta et al., 2021; Kinne et al., 1992; Pitari, 1993; Pitari & Mancini, 2002; Toohey et al., 2014). However, Garfinkel et al.…”
Section: Resultscontrasting
confidence: 96%
“…This result is very different from many previous findings using models in which an intensified BDC was shown (e.g., Abalos et al, 2015;Aquila et al, 2013;DallaSanta et al, 2021;Kinne et al, 1992;Pitari, 1993;Pitari & Mancini, 2002;Toohey et al, 2014). However, Garfinkel et al (2017) and Garcia et al (2011) found the post-volcanic BDC response was an acceleration effect, but mainly in the mid and upper stratosphere, and Garfinkel et al (2017) showed very little change in the BDC in the lower stratosphere (see their Figure 6b).…”
Section: Causes Of the Timing And Longevity Of Heating-driven Volcani...contrasting
confidence: 98%
See 1 more Smart Citation
“…Low-latitude volcanic eruptions (FIG. 1b) are another: aerosol-induced heating warms the tropical lower stratosphere and drives increased upwelling, biasing the QBO toward increased eastward shear and modulating its period, although the exact response depends on the QBO phase at the time of the eruption [151,152]. The response of modelled QBOs to stratospheric sulfate geoengineering is qualitatively similar but model-dependent in its details, as well as depending on the magnitude and latitude of aerosol injection [153][154][155][156].…”
Section: /38mentioning
confidence: 96%
“…In January 2016 and 2020, the anomalous QBO westerlies in the tropical lower stratosphere were unexpectedly interrupted by anomalous QBO easterlies caused by planetary waves propagating from the mid-latitudes toward the equatorial region combined with equatorial convective gravity waves (Osprey et al, 2016;Coy et al, 2017;Kang et al, 2020;Kang and Chun, 2021). There is not yet a clear understanding of how these QBO disruptions are linked to anomalously warm or cold sea surface temperatures (Taguchi, 2010;Schirber, 2015;Dunkerton, 2016;Christiansen et al, 2016;Barton and McCormack, 2017), volcanic aerosols (Kroll et al, 2020;DallaSanta et al, 2021), wildfire smoke (Khaykin et al, 2020;Yu et al, 2021;Peterson et al, 2021) and climate changes (Anstey et al, 2021b). However, recent study based on climate model simulations from phase six of the Coupled Model Intercomparison Project (CMIP6) predicts increased disruption frequencies to the quasi-regular QBO cycle in a changing climate (Osprey et al, 2016;Anstey et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%